Dermatologic principles and practice in oncology : conditions of the skin, hair, and nails in cancer patients - Lacouture, Mario E. (Hoboken, NJ : Wiley-Blackwell, 2013)
"This is the first book to focus on frequent and frequently disabling side effects involving the skin, hair, and nails in cancer patients. It provides detailed descriptions of mechanism-of-action in all current oncology drugs and the clinical presentation and mechanisms underlying their dermatologic side effects, alongside carefully presented treatment recommendations, allowing physicians to significantly enhance their care of patients with cancer. Whereas existing oncology and dermatology textbooks only briefly deal with this topic, this resource offers dermatologists and other practitioners a focused perspective on cancer-related skin conditions"--Provided by publisher.
Machine generated contents note: Section 1 Dermotology and Oncology 1 Epidemiology and Burden of Disease / Beth McLellan and Mario E. Lacouture -- 2 The History of Supportive Oncodermatology / Yevgeniy Balagula1, Steven T. Rosen and Mario E. Lacouture -- 3 Structure and Function of the Integumentary System and the Dermatology Lexicon / Emmy Garber and Amit Garg -- Types of dermatologic reactions / Raed O. Alhusayen, Sandra R. Knowles and Neil H. Shear -- 5 Grading Dermatologic Adverse Events on Clinical Trials using CTCAE v4.0 / Alice Chen, Asha Acharya and Ann Setser -- 6 Psychosocial Issues in Oncology: Clinical management of psychosocial distress, health-related quality of life and special considerations in dermatologic oncology / Lynne I. Wagner and David Cella -- 7 Dermatopathology / James L. Troy and Molly Hinshaw -- Section 2 8 Cancer-Related Dermatologic Disorders / Cindy England Owen and Jeffrey P. Callen -- Section 3 Dermatologic Conditions During Cancer Therapy 9 ORAL MUCOSAL COMPLICATIONS OF CANCER THERAPY / Stephen T. Sonis -- 10 Hair Disorders Associated with Anticancer Agents / Caroline Yeager and Elise A. Olsen -- 11 NAIL ABNORMALITIES IN ONCOLOGY PRACTICE / Robert Baran, Bernard Fouilloux and Caroline Robert -- 12 Pruritus / Tejesh Patel and Gil Yosipovitch -- 13 Management Options for Hot Flashes in Cancer Patients / Amanda R. Moraska and Charles L. Loprinzi -- Section 4 Skin toxicities due to chemotherapy 14 Alkylating agents (Busulfan, ThioTEPA, Mechlorethamine, Melphalan, Chlorambucil, cyclophosphamide, ifosfamide, carmustine, streptozocin, dacarbazine, temozolomide, etoposide, BCNU) / Elisabeth Livingstone, Lisa Zimmer, Larissa Schottler, Dirk Schadendorf1 -- 5 Antimetabolite Reactions (Methotrexate, pemetrexed, capecitabine, cytarabine, gemcitabine, 6MP, 6-TG, fludarabine, cladribine) / Emily Y. Chu and Heidi H. Kong -- 16 Topoisomerase-interacting agents (irinotecan, topotecan, doxorubicin, daunorubicin, epirubicin, idarubicin, mitoxantrone, dactinomycin, etoposide, teniposide) / Tomas Skacel, Roger von Moos and Reinhard Dummer -- 17 Epidermal Growth Factor Receptor Inhibitor Reactions / Yevgeniy Balagula and Mario E. Lacouture -- 18 Small Molecule Kinase Inhibitors / Caroline Robert, Vincent Sibaud and Christine Mateus -- 19 Antimicrotubule agents (Paclitaxel, docetaxel, albumin-bound paclitaxel, vincristine, vinblastine, vi-norelbine, estramustine) / Claus Garbe -- 20 Histone Deacetylase Inhibitors (HDAC inhibitors) Proteasome inhibitors Demethylating Agents Arsenicals Retinoids / Najla Al-Dawsari, Shannon Campbell and Francine Foss -- 21 Miscellaneous Reactions (L-Asparaginase, bleomycin, thalidomide, lenalidomide) / Katharina C. Kaehler, Christine B. Boers-Doets, Mario E. Lacouture and Axel Hauschild -- 22 Skin toxicities due to biotherapy (Interferon-[alpha]2b, Interleukin-2) / Axel Hauschild, Katharina Kaehler and Mario Lacouture -- 23 Monoclonal antibodies / Caroline Robert -- 24 Endocrine Agents / Katherine Szyfelbein and Mario Lacouture -- 25 Agents for the management of hematologic reactions: epotein alpha, darbopoetin, G-CSF, GM-CSF; oprelvekin; low molecular weight heparin; warfarin. / Mee-young Lee and Caroline C. Kim -- 26 RDERMATOLOGICAL PRINCIPLES AND PRACTICE IN ONCOLOGY / Rebecca Wong and Zahra Kassam -- 27 Hematopoietic stem cell transplantation and graft-versus-host disease / Stephanie Hu and Jonathan Cotliar -- 28 Extravasation Reactions / Seppo W. Langer -- 29 Topical Anticancer Therapies / Patricia L. Myskowski -- 30 Life-threatening (Serious) Dermatologic Adverse Events / Milan Anadkat -- 31 Dermatologic infections / Yevgeniy Balagula, Mario E. Lacouture and James I. Ito Section 5 -- 32 Late Dermatologic Conditions / Jennifer Namchoi Section 6 Dermatologic Practice in Oncology 33 Management Algorithms for Dermatologic Adverse Events / Alyx Rosen, Iris Amitay-Laish and Mario E. Lacouture -- 34 Dermatological therapeutics and formulations / Judy H. Borovicka, Jennifer R.S. Gordon, Ann Cameron Haley and Dennis P. West35 Dermatological Techniques and Procedures / Kishwer Nehal, Erica Lee and Robert Eilers -- 36 Appearance-Related Concerns in the Cancer Patient / Amy J. Derick.
Includes bibliographical references and index.
Print version record.
Keywords: Dermatology; Skin -- Diseases; Skin -- Care and hygiene; Skin Diseases -- etiology; Skin Diseases -- psychology; Antineoplastic Agents -- adverse effects; Neoplasms -- complications; Skin Care -- nursing; Skin Manifestations; Dermatology; Skin -- Care and hygiene; Skin -- Diseases; Electronic books